Shaping the future of healthcare: improving quality and safety through integrating simulation into Public Health education - Baldovin, Tatjana; Bassan, Francesco; Bertoncello, Chiara; Buja, Alessandra; Cocchio, Silvia; Fonzo, Marco; Baldo, Vincenzo (Frontiers in Public Health, 2024)
This perspective focuses on the role of healthcare simulation in training and implementing processes aimed at improving the quality of care and patient safety. Evidence of the effectiveness of simulation in improving clinical performance, reducing healthcare costs and raising professional education standards is presented. In light of this evidence, we propose to consider simulation-based education as an integrative training modality in the preparation of health professionals in the field of Public Health. A pilot project is presented with the aim of training professionals capable of further contributing to improving the quality and safety of patients through an interdisciplinary and innovative approach.